Novel Crabtree negative yeast from rumen fluids can improve rumen fermentation and milk quality - Suntara, Chanon (Sci Rep, 2021)
Upgrading the nutritive value of rice straw (RS) is necessary to increase its contribution to enhancing meat and milk production. Present work verified whether novel Crabtree negative yeast inoculant could promote RS utilization, rumen fermentation, and milk quality in tropical crossbred lactating Holstein cows. The new stain of Crabtree negative yeasts (Pichia kudriavzevii KKU20 and Candida tropicalis KKU20) was isolated from the rumen of dairy cattle. This study used 6 multiparous crossbreds between Holstein Frisian × Zebu dairy cows in their mid-lactation period. Dairy cows were randomly allocated to three ensiled RS with various yeast stains including Saccharomyces cerevisiae, P. kudriavzevii KKU20, and C. tropicalis KKU20 according to a 3 × 3 replicated Latin square design. Crabtree-negative yeast (P. kudriavzevii and C. tropicalis) increased the apparent digestibility of dry matter by about 6.9% when compared with Crabtree-positive yeast (S. cerevisiae). Bacterial populations were highest with ensiled RS by C. tropicalis KKU20. Ensiled RS with Crabtree-negative yeasts were significantly increased with total volatile fatty acids, but they did not affect volatile fatty acid profiles. Milk protein precentage was highest at 35.6 g/kg when C. tropicalis was fed, and lowest when applied with S. cerevisiae and P. kudriavzevii KKU20 in ensiled RS at 34.5 and 34.1 g/kg, respectively. Thus, feeding ensiled RS with novel Crabtree negative yeast could improve RS digestion, rumen fermentation, and milk protein content in dairy cows.